Uma análise empírica do índice carbono eficiente (ICO2) no mercado financeiro brasileiro - Schulz, Jéferson Réus da Silva (2018)
The need to stimulate productive practices aimed at the transition from an intensive economy in the use of fossil fuels to a low-carbon economy, is an essential factor capable of reducing the negative externalities of the production process. However, the challenge is to create attractive alternatives for the corporate universe that are capable of stimulating their adherence to this new productive paradigm. The financial market has a monetary capacity capable of promoting actions that minimize the adverse effects caused by climate change, specifically through the operations of resource allocation made possible by the capital market. Thus, it is possible to observe the creation of corporate sustainability indices that generate value for companies and for investors interested in environmental, social and corporate governance (ESG) criteria. The Efficient Carbon Index (ICO2) of the Mercantile and Futures Exchange of the São Paulo Stock Exchange (BM&FBOVESPA) seeks to encourage companies that issue the most negotiated actions to measure, disclose and monitor their greenhouse gas (GHG) to operate in a low carbon economy. The objective of this study is to analyze the current situation of the insertion of sustainability in the Brazilian financial market, through an empirical analysis of ICO2. The study is part of the discussions on sustainability, relating this concept to the financial market, in which a new segment of investors exists in the capital market. These investors consider the socio-environmental impacts of their investments and not only the possibility of obtaining returns of a financial nature, prioritizing a socially responsible conduct of the companies through the application of a screening technique in the composition of the portfolio. This has given rise to socially responsible investment (SRI), which is outside the traditional theoretical approach to finance. The method used in this research consists of analyzing the daily returns of the ICO2 and the Bovespa Index (Ibovespa) based on the application of specific volatility models for the analysis of financial time series A theoretical research is also carried out aiming at the discussion of the problematic that revolves around the insertion of sustainability in the Brazilian financial market, specifically within the framework of a specific action to stimulate the adhesion to a low carbon economy. The results show that the ICO2 is little reactive to market movements, presenting a high inertia and the presence of a leverage effect, evidencing that negative news affects its volatility in a magnitude greater than positive news. In addition, the ICO2 is less volatile to market dynamics than the Ibovespa and is also associated with a lower level of risk. The present study showed that the ICO2, as a specific action to stimulate companies to operate in a low carbon economy, reduces the negative externalities generated by the production process. Thus, the analysis of the Index suggests that the insertion of sustainability in the financial market makes it possible to minimize certain conflicts between economic growth, environmental preservation and social progression by generating value for companies and investors, while reducing the impacts adverse effects of global warming, which also benefits society and the environment. That is, it is possible to reduce the trade-off between the dimensions of sustainable development without generating greater adversities in the economy.